KAJIAN BEBERAPA SIFAT FISIK TANAH DI LAHAN PERTANAMAN STROBERI (Fragaria vesca L) DI KELURAHAN RURUKAN KOTA TOMOHON - Welminama Marice Rumere; Yani E.B. Kamagi; Joice M. Supit (COCOS, 2017)
ABSTRACTThis study aims to determine some physical properties of soil on strawberry plantation land in Rurukan urban Tomohon. The things observed in this research are: Soil Texture Weight Fill Soil Soil Porosity, Soil Permeability and Soil Water Level. Implementation of research activities in the field is done through the stages as follows: Data collection / soil samples were conducted on plots of strawberry plantation at the 15th week after planting consisting of: Land does not use compost and without plastic mulch (K0P0). Land with compost (K) and plastic mulch (P) with compost dose level, namely: 1) 0 ton / ha (K0P1); 2). 15 ton / ha (K1P1); 3). 30 ton / ha (K2P1); 4). 45 ton / ha (K3P1); And 5). 60 tons / ha (K4P1). That with compost treatment with different doses and plastic mulch and soil treatment resulted in differences in the percentage of sand, dust and clay fraction which then gave different values on the weight of soil contents, porosity, permeability and water content in strawberry plantation.Keywords: study. Some physical properties of soil, strawberry plantation land.